R bioinformatics cookbook : use R and bioconductor to perform RNAseq, genomics, data visualization, and bioinformatic analysis /: use R and bioconductor to perform RNAseq, genomics, data visualization, and bioinformatic analysis. (2019) - Maclean, Dan
No abstract available